Notulae ad floram Sloveniae - Pištar, Pina (Hladnikia (Ljubljana), 1998)
Second locality in Slovenia
Keywords: fitogeografija; flora; florae; phytogeography; Slovenia; Slovenija; vegetacija; vegetation